Herbal medicine for amyotrophic lateral sclerosis: A systematic review and meta-analysis - Song, Yuebo; Jia, Qiuyang; Guan, Xiaorui; Kazuo, Sugimoto; Liu, Jia; Duan, Weisong; Feng, Luda; Zhang, Chi; Gao, Ying (Frontiers in Pharmacology, 2022)
Background: The effect of herbal medicine (HM) on amyotrophic lateral sclerosis (ALS) is controversial. Clinical trials investigating HMs continue; however, the use of HM is still questioned. We aimed to systematically review the literature pertaining to the effects and safety of HM in ALS. Methods: Randomised controlled trials (RCTs) that investigated the efficacy of HMs in ALS patients compared to any types of controls were identified. Nine databases and six registers were searched from their inception dates to March 25th, 2022. Per the PRISMA guidelines, trials were identified and extracted. The risk of bias was evaluated using the Cochrane’s tool. Certainty of evidence was assessed as per the GRADE criteria. Forest plots were constructed to assess the effect size and corresponding 95% CIs using fixed-effect models, and random-effect models were employed when required. The primary outcome was the activity limitation measured by validated tools, such as the revised ALS Functional Rating Scale. Results: Twenty studies (N = 1218) were eligible. Of these, only five studies were double-blinded, and two were placebo-controlled. Fourteen HMs (fifty-one single botanicals) were involved; Astragalus mongholicus Bunge, Atractylodes macrocephala Koidz., and Glycyrrhiza glabra L. were commonly used in nine, eight, and six trials, respectively. For delaying activity limitation, Jiweiling injection (MD, 2.84; 95% CI, 1.21 to 4.46; p = 0.0006) and Shenmai injection (SMD, 1.07; 0.69 to 1.45; p < 0.00001) were significantly more efficacious than Riluzole, but the evidence was low quality. For ameliorating motor neuron loss, Jiweiling injection (right abductor pollicis brevis [APB]: MD, 32.42; 7.91 to 56.93; p = 0.01 and left APB: MD, 34.44; 12.85 to 56.03; p = 0.002) was favoured, but the evidence was very low quality. Nine studies reported one hundred and twenty-three adverse events, twenty-six of which occurred in the treatment groups and ninety-seven in the control groups. Conclusions: Very low to low quality of evidence suggests that HMs seem to produce superior treatment responses for ALS without increased risk of adverse events. Additional studies with homogeneous participants, reduced methodological issues, and more efficient outcome measures are required to provide confirmatory evidence.